Readability and Lexical Density of Reading Sections of Tenth Grade English Textbooks in Jordan and Sultanate of Oman: A comparative Study - Mohammad Ahmad Bani Amer; Hussein Abdellateef Baarah (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This research aimed to investigate the reading sections of English textbooks for Tenth grade in Jordan and Sultanate of Oman in terms of their readability and lexical density. To check their readability indices and to assess their lexical density. Data were compiled from reading sections in the textbooks, and quantitatively analyzed through online text analysis software. The findings showed that Jordanian and Omani English textbooks for 10th grade featured the same lexical density and showed that both textbooks include reading sections with low lexical density which indicated that the reading sections were appropriate for 10th grade.  Moreover, the research revealed that, Jordanian English textbook is suitable for 7th grade while Omani English textbook is suitable for 8th grade. It is concluded that Jordanian and Omani English textbooks for 10th grade do not meet the standard requirements of readability indices as they are easier than the expected indices for the target levels.